Effect macrophage activation on infection with Treponema pallidum. - Schell, R (1975)
Infection of rabbits with Treponema pallidum induces nonspecific acquired cellular resistance (ACR) to Listeria monocytogenes. This resistance can be adoptively transferred using thymus-dependent lymphocytes. Since infections that induce ACR are usually brought under control by cellular mechanisms, we sought to determine whether induction of ACR in rabbits stimulates resistance to challenge with T. pallidum. When BCG-infected rabbits which suppressed the growth of Listeria were challenged intravenously with T. pallidum, lesions appeared at the same time and progressed in a fashion similar to that in non-BCG-infected controls. There was a tendency for syphilitic lesions to disseminate more widely in BCG-infected animals and for the lesions to necrose more rapidly in controls. T. pallidum may resist phagocytosis by macrophages, as has been suggested previously, or macrophages may fail to be activated locally in the dermis. Although syphilitic infeciton appears to stimulate ACR, activation of the macrophages may not contribute significantly to the ability of the host to suppress T. pallidum.